Methods of verification of personal data on the basis of the gender analysis of users language of web-communities - Пелещишин, Андрій Миколайович; Федушко, Соломія Степанівна (Eastern-European Journal of Enterprise Technologies, 2010)
This article considers current problem of investigation of verification of personal data based on methods of gender differences of Web-forum member’s messages.